Housing Price Cycle or Housing Price Bubble? Evidence from Economic Phenomenon and Stability Test - Yip, Chee Yin; Wu, Kok Hoong; Aminaddin, Nabilah (2016)
This paper aims to differentiate housing price bubble from a housing price cycle using graphical analysis, cointegrating regression and mean reversion regression. The results suggest that housing market in Malaysia is not facing a bubble at the point of time because there is no sharp upsurge and rapid downfall o f house prices. The recent upsurge in house prices and then followed by a gradual fall is none other than a severe price cycle. This price cycle started in 2009, peaked in 2013 and currently, it slides down rather gradually. l t has been found that this cycle is stable. The main reasons for the price booms are speculative herd instinct and lax in house loan lending policy before 2012. Malaysian government has implemented cooling measures to cool this red hot housing market with success after 2012. However, we are still facing quite serious housing affordability problem as shown by graphical analysis that after 201 1, rise in income is far below the rise in house prices.